Хранителі нелегальних старожитностей в Україні - Гершкович, Я.П. (Археологія, 2005)
У статті розглядається діяльність в Україні приватних колекціонерів археологічних предметів і питання про моральний аспект співробітництва з ними професійних археологів. Когда в начале XVIII в. археология только зарождалась, коллекционирование было единственным способом получения знаний о прошлом. Сейчас положение кардинально изменилось — археологические предметы стали товаром. По всему миру на нижних ступенях этого бизнеса задействована широкая сеть грабителей, а на верхних — дилеров, скупщиков и коллекционеров. Украина не является исключением. Большая часть экспонатов, представленных на выставках частных коллекций в Украине, или получена из незаконных раскопок, или является фальсификатом. Назрела необходимость разработки Кодекса археологической этики, в котором был бы учтен международный опыт и рекомендации профессиональным археологам не обеспечивать экспертизу и не давать рекомендации дилерам или частным коллекционерам. In the beginning of the 18th century, when the archeology was just rising, collecting was the only way to get the knowledge about the past. The situation has fundamentally changed by now. Archeological finds are sold and bought these days. There is a wide network of robbers at the lower level of this worldwide business, as well as dealers and collectors on the upper one. Ukraine is not an exception. Most of the items displayed at the exhibitions of private collections in Ukraine either come from illegal excavations or occure to be caunterfeits. There is an urgent necessity to develop the Code of the Archeological Ethics taking into account the international experience and to recommend to professional archeologists not to provide examinations and any recommendations to the dealers or private collectors.